Surpassing 90% Shockley–Queisser VOC limit in 1.79 eV wide-bandgap perovskite solar cells using bromine-substituted self-assembled monolayers - Zhouyin Wei; Zhou, Qilin; Niu, Xiuxiu; Liu, Shunchang; Dong, Zijing; Liang, Haoming; Chen, Jinxi; Shi, Zhuojie; Wang, Xi; Jia, Zhenrong; Guo, Xiao; Guo, Renjun; et al. (Energy & environmental science, 2025)
All-perovskite tandem solar cells (TSCs) hold the promise of surpassing the efficiency limits of single-junction solar cells. However, enhancing TSC efficiency faces the challenge of significant open-circuit voltage (VOC) loss in the wide-bandgap (WBG) subcell. In this study, we employed a bromine-substitution strategy to develop a novel self-assembled monolayer, (4-(3,11-dibromo-7H-dibenzo[c,g]carbazol-7-yl)butyl)phosphonic acid (DCB-Br-2), as the hole-transporting layer for 1.79-eV WBG perovskite solar cells. The bromine in DCB-Br-2 donates a pair of non-bonded electrons to uncoordinated Pb2+ ions or halide vacancies, enhancing interaction with the perovskite layer and suppressing interfacial non-radiative recombination. DCB-Br-2 also adjusts energy level alignment, facilitating fast hole extraction. The optimized WBG solar cell achieved a maximum VOC of 1.37 V, surpassing 90% of the Shockley–Queisser limit. Combined with a 1.25-eV narrow-bandgap subcell, this enabled a two-terminal all-perovskite TSC with a champion power conversion efficiency of 27.70%, advancing the development of high-performance tandem devices.